Environmental Victims and Resistance to State Crime Through Transnational Activism - White, Rob (Social justice, 2009)
In this article the author examines state crimes against the environment. He defines such criminality as pollution, overuse of sustainable industries such as forestry and fishery for financial gain, and the exploitation of humans and animals by a minority at the expense of the majority public good. The central focus of the article is an examination of environmental activism and the actions of victims. Also explored is the fact that the state can simultaneously be the defender of the environment and the aggressor against it.